Catalytic effect of oil shale ash on CO2 gasification of leached wheat straw and reed chars. (1st June 2018) - Link, Siim; Tran, Khanh-Quang; Bach, Quang-Vu; Yrjas, Patrik; Lindberg, Daniel; Arvelakis, Stelios; Rosin, Argo
Abstract: Oil shale ash is a material that could be used as a low cost catalyst for biomass gasification processes. This article analyses the catalytic effect of oil shale ash on CO2 gasification of reed and leached wheat straw chars. A thermogravimetric analyser operated at atmospheric pressure and two different partial pressures of CO2 such as 0.09 atm and 1 atm were applied. The results indicate that oil shale ash has positive effect on char reactivity at the CO2 partial pressure of 0.09 atm: the addition of oil shale ash by 30% to reed char lowered the reaction time by 1.3 times and to leached wheat straw char by 1.4 times. At the partial pressure of CO2 1 atm, the addition of oil shale ash resulted in the negative effect on the char conversion due to the binding of CO2 . The average calculated CO2 binding capacity of oil shale ash was 13.7 mg CO2 per 100 mg of oil shale ash. Abstract : The impact of oil shale ash on gasification is dependent on partial pressure of CO2 . Oil shale ash could act as catalyst under atmospheric gasification conditions. Oil shale ash could bind CO2 under pressurized gasification conditions.